Effect of phacoemulsification on facility of outflow. Issue 11 (13th April 2018) - Alaghband, Pouya; Beltran-Agulló, Laura; Galvis, Elizabeth Angela; Overby, Darryl R; Lim, Kin Sheng
Abstract : Purpose: Phacoemulsification has been shown to reduce intraocular pressure (IOP). The mechanism of action is thought to be via increased trabecular outflow facility. However, studies on the relationship between phacoemulsification and outflow facility have been inconsistent. This study intended to examine the change in electronic Schiotz tonographic outflow facility (TOF) and IOP measurements following phacoemulsification. Methods: Patients who were due to undergo a standard clear corneal incision phacoemulsification with intraocular lens (IOL) implantation, at St Thomas' Hospital, were invited to participate in this study. IOP was measured using Goldmann's applanation tonometer, and TOF was measured by electronic Schiotz tonography at baseline and at 3, 6 and 12 months postoperatively. Results: Forty-one patients were recruited. Tonography data for 27 patients were reliable and available at all time points. Eleven cases had primary open angle glaucoma and cataract, while 16 patients had cataract only. Mean IOP reduced at every time point postoperatively significantly compared with baseline. TOF improved significantly after cataract extraction at all time points (baseline of 0.14±0.06 vs 0.18±0.09 at 3 months, P=0.02 and 0.20±0.09 at 6 months, P=0.003, 0.17±0.07 µL/min mmHg at 12 months, P=0.04). Five contralateral eyes of patients with cataracts only who did not have any intraocular surgery during the follow-up period were used as comparison. Their IOP and TOF did not change significantly at any postoperative visits. Conclusion: This is the first study using electronic Schiotz tonography with documented anterior chamber depth and gonioscopy after modern cataract surgery (CS) with phacoemulsification and IOL implantation. We demonstrated that phacoemulsification increases TOF and this fully accounts for the IOP reduction following CS. ISTCRN registration number: ISRCTN04247738 .